Spectrum of Thyroid Illness in COVID-19 - Rakhshinda Jabeen, Santosh Kumar Sidhwani, Muhammad Rehan, Rajesh Kuma, Adil Faraz (Pakistan Journal of Medical & Health Sciences, 2022)
Background: De novo thyroid dysfunction can occur as a result of COVID-1. Patients have diverse manifestations of thyroid illness, ranging from asymptomatic hyperthyroidism to secondary hyperthyroidism. Aim: To evaluate various thyroid diseases and compare them to mortality and clinicopathological features. Methods: After approval from the institutional ethical review board, this observational cross sectional study was carried out at a private sector hospital in Karachi. Patients diagnosed with COVID-19 admitted between December 2020 to May 2021 were recruited using consecutive sampling. Patients who did not give informed consent and had known thyroid disorders or history of thyroidectomy were excluded. To analyse the relationship between thyroid laboratory reports, and clinicopathological features, the Chi-square test and “Fischer’s exact test” were utilised. SPSS version 21 was used for statistical analysis. A statistically significant P value of 0.05 was used. Results: Majority of the patients 105(72.9%) had higher FT3 levels and none of them reported with the decreased levels. 88(61.1%) came up with the higher FT4 levels while 9(6.3%) reported with decreased FT4. 9(6.3%) and 6(4.2%) were positive for the anti-thyroperoxidase and anti-thyroglobulin antibodies. The results showed statistical significance for free FT4 (p value 0.018), anti-TG (p-value 0.001) and anti-TP antibodies (p value 0.005). Conclusion: COVID-19 patients had a high frequency of thyroid abnormalities. Thyroid dysfunction appears to fluctuate over time and to recover slowly and naturally.